Strategi Detterence Siber Indonesia terhadap Ancaman Proxy State Actor - Aminarti Fithri Amalia; Wira Atman (Aliansi: Jurnal Hukum, Pendidikan dan Sosial Humaniora, 2025)
Advances in information technology have increased the country's vulnerability to cyber threats, including attacks by proxy state actors that are difficult to track and account for. Indonesia as a developing country faces challenges in formulating an effective cyber defense strategy. This study aims to analyze Indonesia's cyber deterrence strategy in dealing with proxy state actor threats, and to compare it with the approaches taken by Singapore and South Korea. The research method used is a qualitative study with a comparative approach, examining policies, institutional capacity, and the effectiveness of strategy implementation in each country. Initial findings indicate that Indonesia is still in the early stages of developing an integrated cyber deterrence strategy, especially in terms of attribution, cyber diplomacy, and strengthening national capacity. Singapore and South Korea have implemented a more systematic approach, including regional cooperation and cross-sector policy integration. The results of this study are expected to contribute to the formulation of national policies in strengthening Indonesia's digital resilience and sovereignty.